Lifestyle monitoring and indignity procedures (Academic Journal of Internal Affairs, 2017)
The author provides an overview of police lifestyle monitoring and indignity procedures in Hungary by reviewing the legislation in force, practical examples and case studies.
Keywords: police lifestyle; monitoring; case study